2010
DOI: 10.4314/br.v8i1.62550
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Some Leaf Extracts on Some Seed Borne Fungi of African Yam Bean (<i>Sphenostylis stenocarpa</i> Hochest Ex. A. Rich)

Abstract: The antifungal effect of ethanol leaf extracts of five plants, (viz. Jatrohpa curcas L, Newbouldia laevis (P. Beauv.) seem. Ex Bureau, Ficus exasperate Vahl, Parkia biglobosa (Jacq.) and Cassia alata L.) Seed plus 30 wettable solvent (WS) and Water on some Seed borne fungi: Aspergillus niger and Fusarium oxysporium of African yam bean (Sphenostylis stenocarpa) seeds was studied in vitro using agar plate method of isolation. The efficacy of the treatments was tested separately on the individual fungal isolates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a study by [47] the phytochemical screening of Jatropha curcas leaf revealed the presence of tannins, saponins, flavonoids, alkaloids, oxalates and cardiac glycosides while [48] reported that root and latex extracts of J.curcas plant contained phenolics, flavonoid and saponins. Other phytochemical screening reported by [49] indicated the presence of nine different phytochemicals form Jatropha curcas in varying degrees.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…In a study by [47] the phytochemical screening of Jatropha curcas leaf revealed the presence of tannins, saponins, flavonoids, alkaloids, oxalates and cardiac glycosides while [48] reported that root and latex extracts of J.curcas plant contained phenolics, flavonoid and saponins. Other phytochemical screening reported by [49] indicated the presence of nine different phytochemicals form Jatropha curcas in varying degrees.…”
Section: Phytochemical Analysismentioning
confidence: 99%